2020
DOI: 10.5194/esurf-2020-34
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coastal Change Patterns from Time Series Clustering of Permanent Laser Scan Data

Abstract: Abstract. Sandy coasts are constantly changing environments governed by complex interacting processes. Permanent laser scanning is a promising technique to monitor such coastal areas and support analysis of geomorphological deformation processes. This novel technique delivers 3D representations of a part of the coast at hourly temporal and centimetre spatial resolution and allows to observe small scale changes in elevation over extended periods of time. These observations have the potential to improve … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…They are characterized by a large maximum height change and shorter duration. These aspects indicate that cluster 5 shows anthropogenic deposition by bulldozers, as it has already been identified that such activities occur in this part of the beach (Kuschnerus et al, 2021).…”
Section: Hierarchical Clusteringmentioning
confidence: 53%
See 1 more Smart Citation
“…They are characterized by a large maximum height change and shorter duration. These aspects indicate that cluster 5 shows anthropogenic deposition by bulldozers, as it has already been identified that such activities occur in this part of the beach (Kuschnerus et al, 2021).…”
Section: Hierarchical Clusteringmentioning
confidence: 53%
“…Previous research on morphological change extraction from such four-dimensional (4D) datasets, was focused on full time series clustering, and as such, identifying areas of homogeneous surface change over the full time series (Kuschnerus et al, 2021;Winiwarter et al, 2022). A drawback of these methods is that individual occurrences of surface activity are not separated.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been explored to detect and localise changes in permanent laser scanning data, mostly focused on analysing elevation changes (see for example (Anders et al, 2021), (Kuschnerus et al, 2021a), (Brand et al, 2019)). General analysis of time series from remote sensing data for sudden changes has been presented for example by (Verbesselt et al, 2010) and (Kuenzer et al, 2015).…”
Section: Related Workmentioning
confidence: 99%
“…A surface to surface approximation comparison is shown in Figure 12 but not for other examples: it could indicate misleading differences in areas with missing information, i.e., with sparse and varying coverage. Kuschnerus et al (2021) stated that on a small area of the beach at the bottom of a footpath, sand accumulated after a storm. Afterwards, the beach was cleared, and the superfluous sand forms a pile.…”
Section: Surface Approximation To Study Deformation Patternmentioning
confidence: 99%